Gas separation through polyurethane–ZnO mixed matrix membranes and mathematical modeling of the interfacial morphology. (1st December 2020) - Fakhar, Afsaneh; Maghami, Saeid; Sameti, Elham; Shekari, Monireh; Sadeghi, Morteza
Abstract: A series of polyurethane/ZnO membranes was fabricated via thermal phase inversion of the solution of polymer/nanoparticle in N, N ‐dimethylformamide solvent. The polyurethane synthesis was done via two‐step polymerization method using polytetramethylene glycol, isophorone diisocyanate, and 1, 4‐butanediol in the ratio of 1:3:2. Different concentrations of zinc oxide nanoparticles (5, 10, 15, and 20) were incorporated into the polyurethane matrix. FTIR, SEM, and X‐Ray analysis were performed to characterize the membranes. FTIR and SEM results suggests an increment in the phase mixing of polyurethane with ZnO loading. Gas permeation performance through polyurethane‐ZnO mixed matrix membranes with ZnO loading by as much as 20 wt% were elucidated for pure N2, O2, CH4, and CO2 and gases. Based on the results, all permeability values decreased as the loading of ZnO nanoparticles increased, whereas CO2 /N2 and CO2 /CH4 selectivities increased. Moreover, interfacial structure of the polyurethane/ZnO nanocomposites were characterized by molecular probing approach. The results revealed the presence of a rigidified polymer chain layer with 65 ± 6 Å thickness around the ZnO nanoparticles. Abstract :